Development Lies in Corporate Processes - Fenyves, László (International Journal of Engineering and Management Sciences, 2020)
Nowadays, our rapidly evolving world is characterized by constant change. Organizations need to be prepared and responsive to these systematic changes to compete in the marketplace. Today nothing is constant or predictable because the organization is driven by the "3 C" force (customers, competition, change). Rapid adaptation to ever-changing circumstances requires companies to move from structured organizations based on traditional functions to process-based management. By using state-of-the-art process management procedures, organizations can be made transparent, analysable, measurable, and continually improving, and help companies increase their performance and organizational flexibility, and reduce costs. It also helps to recognize when it is necessary to change a process for an effect. In the event of creating well-organized processes, companies are more responsive to changes in the market, allowing them to operate more efficiently, and to carry out development activities easier. Nowadays, development as a new framework focuses primarily on digitalisation, which is challenging for companies to adapt but without this, they would be left behind in the competition. These challenges require radical changes and transformations in the lives of many organizations, which are difficult to achieve. With the development of process-based enterprise management, not just multinational companies can improve their operation, but small and medium-sized enterprises can also move towards digitalization thus inducing development for not only their own but for the economy as a whole.